Wearable Electrochemical Glucose Sensors for Fluid Monitoring: Advances and Challenges in Non-Invasive and Minimally Invasive Technologies - Ming Wang; Junjie Zheng; Ge Zhang; Shiyan Lu; Jinli Zhou (Biosensors)
This review highlights the latest developments in wearable electrochemical glucose sensors, focusing on their transition from invasive to non-invasive and minimally invasive designs. We discuss the underlying mechanisms, performance metrics, and practical challenges of these technologies, emphasizing their potential to revolutionize diabetes care. Additionally, we explore the motivation behind this review: to provide a comprehensive analysis of emerging sensing platforms, assess their clinical applicability, and identify key research gaps that need addressing to achieve reliable, long-term glucose monitoring. By evaluating electrochemical sensors based on tears, saliva, sweat, urine, and interstitial fluid, this work aims to guide future innovations toward more accessible, accurate, and user-friendly solutions for diabetic patients, ultimately improving their quality of life and disease management outcomes.